Shiga toxins, glycosphingolipid diversity, and endothelial cell injury - Müthing, Johannes; Schweppe, Christian H; Karch, Helge; Friedrich, Alexander W (Thrombosis and haemostasis, 2009)
Shiga toxin (Stx)-producing Escherichia coli (STEC) cause an enteric illness that results in a spectrum of outcomes ranging from asymptomatic carriage to uncomplicated diarrhea, bloody diarrhea, and the postdiarrheal haemolytic uremic syndrome (HUS), which leads to renal and other organ microvascular thrombosis. Binding of Stx to the glycosphingolipid (GSL) globotriaosylceramide (Gb3Cer/CD77) on endothelial cells followed by receptor-mediated endocytosis is the linchpin in STEC-mediated disease. Only GSLs that associate strongly with lipid rafts appear to carry Stxs retrogradely from the plasma membrane through the Golgi apparatus to the endoplasmic reticulum where they are translocated to the cytosol and exert their toxic function. Thus, the biophysical features of the lipid moiety of GSL receptors may influence its incorporation into certain membrane domains and thereby affect toxin destination. Consequently, a detailed structural analysis of Stx-binding GSLs is required to illuminate the molecular causes that may underlie the different Stx susceptibilities of endothelial cells derived from various vascular beds. Solid phase overlay binding assays of thin-layer chromatography (TLC)-separated GSL preparations employing specific antibodies and/or Stxs in conjunction with anti-Stx-antibodies are commonly used for the identification of Stx-binding GSLs. Such GSL-profiling combined with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) represents a convenient strategy to structurally characterize Stx-receptors from any biological sources such as primary cells, cell lines, or organs. This approach may be helpful to gain insights into Stx-induced impairment of target cells that is suggested to originate at least partly from the structural heterogeneity of the cellular ligands of Stxs.